Analysis of Economic Factors in the Context of Healthcare Reform in Ukraine - Inozemtsev, Serhiy (Theoretical and Practical Research in Economic Fields, 2026)
The study aimed to assess the impact of economic factors on the healthcare system renewal in Ukraine. The study analysed key regulatory documents that affect healthcare financing and management and compares the Ukrainian model with those of other European countries, such as Poland, Germany, the Czech Republic and Switzerland. To obtain the results, data for 2019-2025, including official statistics on sector financing and access to healthcare services, were used. The main findings of the study indicate significant regional disparities in access to healthcare services in Ukraine, which appear to be associated with the uneven distribution of financial resources. The available data suggest that healthcare reform based on the principle of “money follows the patient” has improved funding for healthcare facilities in large cities, while rural facilities tend to remain comparatively underfunded. In addition, the study determined that higher incomes provide better access to healthcare services, while people with lower incomes face financial barriers and informal payments, which worsen access to healthcare. Comparisons with healthcare models in Poland, Germany and the Czech Republic demonstrated that systems with compulsory health insurance provide greater financial stability and equal access to healthcare services. The Ukrainian system requires significant reforms to address regional disparities and improve the efficiency of financing. The findings highlight the need to improve the mechanisms for allocating financial resources, particularly for rural areas, and to attract additional private investment to modernise healthcare facilities.